(3GdaQbs - (3CHh eMeO KGHJ Hf CHi KGHJ SYjO Gdchais; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GHJOGA cJGH GdaQb (B: (3bGd KGHJ Hf CHj KGHJ (B: (3gPG cJGH eG NGda ajg JSejI LhGQM GdEfSGf JSejI LhGQM PhGJ GdCQHY ef GdHgGFe hGdSHGY s
(3BNQgG (B:s
(3GdJfGS (B: (3GdSjQ GdSQjY GdTOjO Ci dJGTjFkG ef GdShjb hZjQg dfQJMd bHd Cf jOQcfG GdWdH Je cJGH GdaQb hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B152 - (3U(B213s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B170 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs